Burnout and Compassion Fatigue Among Nurses: Causes, Consequences and Strategies for Resilience and Self Care - Chioma Ibe; Solomon Justina Adanma Nwagwu; Kaunda Julia Ibebuike; Chinelo Clare Vincent; Anthonia Chinwendu Emesowum; Onyekwuo Festa Chinonye; Emmanuel Ifeanyi Obeagu (Research Output Journal of Public Health and Medicine, 2026)
Burnout and compassion fatigue have become increasingly prevalent among nurses due to the demanding nature of the nursing profession and the continuous exposure to physical, emotional, and psychological stressors. These conditions not only affect the well-being of nurses but also compromise the quality and safety of patient care. This seminar explores burnout and compassion fatigue among nurses by examining their causes, consequences, and strategies for resilience and self-care. The major causes discussed include excessive workload, inadequate staffing, prolonged working hours, emotional exhaustion, exposure to patients’ pain and suffering, lack of organizational support, poor work-life balance, and insufficient coping mechanisms. The seminar further highlights the consequences of burnout and compassion fatigue, such as decreased job satisfaction, reduced productivity, increased absenteeism, high staff turnover, impaired professional judgment, medical errors, poor patient outcomes, and adverse effects on nurses’ physical and mental health. Emphasis is placed on evidence-based strategies that promote resilience and self-care, including stress management, mindfulness practices, regular physical exercise, adequate sleep, healthy nutrition, peer and social support, professional counseling, continuous professional development, and organizational interventions such as supportive leadership, adequate staffing, and employee wellness programs. Building resilience enables nurses to adapt effectively to workplace challenges while maintaining their emotional well-being and professional competence. The seminar concludes that preventing and managing burnout and compassion fatigue require a collaborative approach involving individual nurses, healthcare institutions, and policymakers. Implementing effective resilience and self-care strategies is essential for enhancing nurses’ well-being, improving patient care outcomes, strengthening workforce retention, and promoting a healthier and more sustainable healthcare system. Keywords: Burnout; Compassion Fatigue; Nurses; Resilience; Self-Care.